INVESTIGATION OF NEUROPATHIC PAIN AND RELATED FACTORS IN PATIENTS WITH ANKYLOSING SPONDYLITIS - Elbasti, M. S. (Elsevier, 2025)
[Abstract Not Available]
Keywords: Physical therapy; Physiotherapy; Qualitative research; and Physical Activity